STUDI MOTIVASI KERJA PEGAWAI KANTOR CAMAT GUNUNG KERINCI - Ikhsan, Mhd (journal of RESIDU, 2018)
Research this aim deskripted about Moivation Activity of Office subdistrict head Gunung Kerinci. Focus of research which lift to motivation increase effectiveness. Include : effectiveness in performance succes a job . and also to the which factors and obstruct implement subdistrict head Gunung Kerinci. Technique of data cellecting which use is research qualitatives. Source of document obtain get from key informan and informan by using tecnique purposive sampling that is tecnique determination sampel which accomodate with purpose to research.Result of research show that motivation activity on offfice subdistrict head Gunung Kerinci pertained hve a good enough. Factors of which pickaba in execution motivation prima facie job activity is medium the complete infrastructure and good which comunications. Matters this can improve, repaired all factor able to pursoed in execution evalution motivation prima facie job activity is medium.   Keyword : Motivation activity and office subdistrict Head